Soil solution and rice nutrition under liming and water management in a soil from Amazonian natural fields - Radmann, Vairton; de Sousa, Rogério Oliveira; Weinert, Cristiano; Jordão, Half Weinberg Corrêa [UNESP]; Carlos, Filipe Selau (Revista Brasileira de Ciencia do Solo, 2023)
Soils of natural grasslands in the Amazon region play an essential role in local food production and preservation of the Amazon rainforest. However, in general, these soils have high acidity, which limits irrigated rice production. The objective of this study was to evaluate the effect of liming and irrigation management on the dynamics of soil reduction, nutrients in the soil solution, nutrition, and aboveground plant biomass in natural fields soil in southern Amazonia, Brazil. The experiment evaluated the correction factors for soil acidity and irrigation management, flooded and saturated soil. The experiment was carried in pots in a greenhouse. Liming reduced the Eh of the soil and had a higher influence than the soil irrigation condition. Liming also had a higher influence on soil pH than irrigation conditions. Liming and saturated soil had the lowest Fe content in the soil solution. Higher Ca and Mg contents were observed in the soil solution under liming and flood irrigation. Thus, liming is an essential strategy to improve chemical conditions for plant development in the soil of natural Amazonian grasslands and can be used in conjunction with saturated irrigation, which is more efficient in using water and reduces the effects of iron toxicity.
Keywords: Gleysol; iron reduction; paddy field; redox reactions; soil acidity